Ambipolar charge transport in a non-fullerene acceptor - Franziska H. Hasenburg; Kun-Han Lin; Bas van der Zee; Paul W. M. Blom; Denis Andrienko; Gert-Jan A. H. Wetzelaer (APL Materials, 2023)
Charge transport is one of the key factors in the operation of organic solar cells. Here, we investigate the electron and hole transport in the non-fullerene acceptor (NFA) IT-4F, by a combination of space-charge-limited current measurements and multiscale molecular simulations. The electron and hole mobilities are fairly balanced, amounting to 2.9 × 10−4 cm2 V−1 s−1 for electrons and 2.0 × 10−5 cm2 V−1 s−1 for holes. Orientational ordering and electronic couplings facilitate a better charge-percolating network for electrons than for holes, while ambipolarity itself is due to sufficiently high electron affinity and low ionization energy typical for narrow-gap NFAs. Our findings provide a molecular-level understanding of the balanced hole and electron transport in an archetypical NFA, which may play a key role in exciton diffusion and photogenerated hole transfer in organic solar cells.